SANITATION OF CHICKEN SLAUGHTERING BUSSINESS WITH CRITICAL DISORDERS - Radillah, Radillah; Alim, Andi; Hidayat, Hidayat (PROMOTIF: Jurnal Kesehatan Masyarakat, 2017)
The existence of Chicken Slaughtering Bussiness (CSB) being located in the middle of the settlement makes people disturbed the comfort of waste generated such as smell, sewage, vector to the people who live around the CSB in Urban Village East Bara-Baraya. The purpose of this research is to know the description of environmental sanitation of Chicken Slaughtering Bussiness with disturbance of comfort, in Urban Village East Bara-Baraya District of Makassar city. The method of this research is descriptive with observation approach to see description between disturbance of comfort, smell, liquid waste, and vector. The number of samples in this study was 42 samples. The results showed that most of the CSB in Urban Village East Bara-Baraya caused an unpleasant smell that made the community around the slaughterhouse feel uncomfortable. Waste disposal from cutting process is thrown away to drainage channel causing unpleasant odour which makes the society of Urban Village East Bara-Baraya disturbed comfort. There is a vector around the dumpster and sewerage channel of Chicken Slaughtering Bussiness that makes the transmission of seeds of disease to the community around CSB so that often family members affected by diseases such as diarrhoea, fever and wormy in children. Suggestions for the research are suggested to CSB owners to maintain the cleanliness of chicken coop and throw away the remaining processed chicken away from community settlements in order not to cause odour. The need for the government to issue a policy on the prohibition of disposing waste chicken processed waste into sewerage channels around the community environment of Urban Village East Bara-Baraya. It is expected that health workers to provide counselling on how to prevent the occurrence of infectious diseases caused by existing vectors in the community of Urban Village East Bara-Baraya. Keywords: Chicken Slaughtering Bussiness, Sanitation and Vektor